Nghiên cứu tổng hợp BiFeO3 bằng phương pháp thủy nhiệt - Nhiệm, Đào Ngọc; Dũng, Đoàn Trung; Hà Chi, Nguyễn Thị; Văn, Nguyễn Đức (Vietnam Journal of Chemistry, 2015)
Bismuth ferrite (BiFeO3) powders were synthesized by hydrothermal method using Bi(NO3)3 and Fe(NO3)3, acetic acid and KOH as starting materials. The effects of reaction time, hydrothermal temperature and molar ratio of acetic acid/metal on the formation of BiFeO3 were investigated. X-ray diffraction (XRD) and field-emission scanning electron microscopy (FESEM) were used to characterize synthesized oxide powders. The results showed that single-phase BiFeO3 with the average grain size < 100 nm was obtained at hydrothermal temperature as low as 180 oC for 12 hours.